Análise estratigráfica do grupo Macaúbas no domínio meridional da Serra do Espinhaço, Minas Gerais - Lucio Mauro Soares Fraga (2013)
This doctoral thesis concentrates on sequential stratigraphic analysis, isotope chemostratigraphy (C, O and Sr) and the study of stromatolites (morphology and sedimentary environments) of metasedimentary sequences of Macaúbas Group, in the northeast of the Southern Espinhaço Ridge. Thus, the stratigraphy of the Macaúbas Group in the study area, comprises three depositional sequences: (1) Duas Barras Sequence, further subdivided into the AF 1 metarenites and metaconglomerates deposited in a Fan Delta I system, AF 2 - metapelites with stromatolitic dolostone lenses deposited in tidal flat system for a transgressive tract, (2) Tijucuçu Sequence, constituted by AF 3 - metarenites with lithic fragments and fine metarenites deposited in a Fan Delta II system and AF 4 - carbonate and graphitic metapelitic rocks, laminated calcarenites and calcilutites deposited on a plataformal system in high system tract, (3) Glacial Sequence subdivided into the AF Diamictítica with massives and/or laminated metadiamictites, deposited in glaciocontinental and glacio-marine systems and AF Areno-pelítica, consisting of metarhytmites with dropstones, laminated metarenites and metapelites deposited in a glacio-marine system. The deformation of these rocks is related to the Brasiliano event (560-490 Ma) and was responsible for asymmetric folds and subverticalized main foliation (S1), marked by the orientation of micaceous plans beyond the regional metamorphic paragenesis (chlorite + epidote + calcite + biotite ± spessartite). In the eastern portion, there is a spaced crenulation cleavage (S2 foliation), which deforms the planes S1, representing the second deformation phase, influenced by ZCDCA (Distentional Shear Zone Chapada Acauã). In the dolostone lenses of Duas Barras Sequence (AF 2) it was characterized an association of branched and conical stromatolites (Conophyton - Jacutophyton), deposited in a coastal environment dominated by tides (tidal flat) and shallow (shallow subtidal). C and O-isotope chemostratigraphic study performed with detailed sampling of dolostones of AF 2, limestone of AF 4, dolostones of the Rio Pardo Grande Formation (Espinhaço Supergroup) and further carbonates of Bambuí Group. C and O-isotopes in carbonate rocks of the Macaúbas Group suggest that AF 4 was deposited during a very hot and dry climate, with low input of continental sediments. The 86Sr/87Sr ratios (0.7072 and 0.7075) found in the limestone of Tijucuçu Sequence, below packages of metadiamictites of Glacial Sequence, are similar to those found in the Cryogenian period, post- Sturtian (700-650 Ma). In metarenites of AF 3, the age of the yongest zircon found U/Pb 1115 Ma can be inferred as the minimum age for the ultimate of the sedimentation in AF 3 of Tijucuçu Sequence. The younger magmatic zircon found in the intrusive rocks of AF 1 (Duas Barras Sequence) has U / Pb 1246 ± 17 Ma age. However, these rocks are contaminated with inherited magmatic zircons and detrital zircons, losing their reference age of magmatism.